Narasi Toleransi Beragama di Media Sosial (Studi Atas Akun Twitter Komunitas Katolik Garis Lucu) - Arina Al Ayya (2022)
The era of the Covid-19 pandemic in Indonesia, which has been going on since the beginning of 2020, has had quite an impact on people’s lives, one of which is related to the rules for limiting social interaction. This policy on the one hand forces people to limit direct interaction, and on the other hand opens opportunities for virtual interaction, in this case social media. In the period of the pandemic until now, which is claimed to have entered an endemic period, the interactions built by the community in the digital world do not necessarily occur without a single obstacle. The consequences are fatal if there is misunderstanding in the name of identity, one of which is about religious identity. So then, the role of the social media universe, especially accounts that are managed non-personally becomes very important in maintaining the integrity of religious tolerance in the digital world. This article tries to discuss the religious tolerance narrative built by the twitter account of the Komunitas Katolik Garis Lucu. This community is one of the GL (Garis Lucu) communities that thrive on twitter social media. This research uses a qualitative-descriptive approach and Roland Barthes semiotic analysis. As a result, it was found that the twitter account of the Kaomunitas Katolik Garis Luc played a role in building the creation of communiation within the scope of multiculturalism by using typical writings in the form of jokes, memes, and satire. This communication can directly and/or indirectly trigger adaptability, flexibility, and tolerance in accepting differences, specifically on religion.